Prevalence of malocclusions in a group of mexican university students and its possible association with age, sex, and socioeconomic status, 2009 - Murrieta-Pruneda, José Francisco; Arrieta-Ortega, Claudia Lorena; Juárez-López, Lilia Adriana; Linares-Vieyra, Celia; González-Guevara, Martha Beatriz; Meléndez-Ocampo, Arcelia (Revista Facultad de Odontología Universidad de Antioquia, 2012)
Introduction: dental occlusion refers to the relationships of teeth at rest; it may be altered by a variety of factors. The purpose of this study was to evaluate the prevalence of dental malocclusions and their possible relations to age, sex, and socioeconomic status in a group of university students. Methods: the epidemiological survey was conducted in two moments: application of a questionnaire, and an oral examination. Two examiners were standardized for this purpose (Cr = 0.03, Ca = 0.89, k = 0.902). Results: 47.7% of the students come from the middle class. 13.2% presented normal occlusion, and 86.8% had dental malocclusion. Their distribution per age, sex, and socioeconomic status did not show statistically significant differences. Concerning malocclusion classification, the most common one was Class I (37.3%), a figure which happened to be lower than expected, in comparison to the same condition in similar populations. Conclusions: the only conclusion drawn from this study is that socioeconomic status is not a factor associated to the frequency of dental occlusion classification in this population, so there might be other factors to be evaluated, such as cultural and educational factors.